A significant northward range extension of Munchique Wood-wren (Henicorhina negreti) in the western Andes of Colombia: Una extensión significativa de la distribución del cucarachero de Munchique (Henicorhina negreti) hacia el norte en la Cordillera Occidental de Colombia (Ornitología Colombiana, 2021)
Henicorhina negreti is reported from the Department of Antioquia in the Western Andes of Colombia, 350 km north of the type-locality. This finding implies that the species is much more widespread than previously thought and calls for a reexamination of its conservation status.